Surfactant Protein-D (SP-D) serum levels as a predictor of COVID-19 severity and mortality: A systematic review and meta-analysis - Kacper Dziedzic; Michal Pruc; Gabriella Nucera; Damian Swieczkowski; Maciej Koselak; Lukasz Szarpak (Advances in Medicine, Psychology, and Public Health)
Introduction: This study investigates the diagnostic and prognostic potential of Surfactant Protein D (SP-D), in distinguishing COVID-19 patients from healthy controls and predicting outcomes in infected individuals. Through a comprehensive systematic review and meta-analysis, we aim to elucidate the role of SP-D in the clinical management of COVID-19, addressing a crucial gap in current biomarker research. Methods: We searched PubMed, Embase, Web of Science, and Scopus, for articles published in English up to January 21, 2024. We employed a systematic review and meta-analysis approach, searching multiple databases for studies that measured SP-D levels in COVID-19 patients and healthy controls. The inclusion criteria were strictly defined to ensure the selection of studies with high-quality data, and statistical analyses were performed to assess the diagnostic and prognostic value of SP-D in the context of COVID-19. Results: Twelve studies were included in this systematic review and meta-analysis. Pooled analysis showed that SP-D levels among those groups of patients varied and amounted to 44.38±74.71 vs. 21.29±31.8, respectively (SMD = 1.39; 95%CI: 0.35 to 2.43; p=0.009). Pooled analysis of SP-D values among severe and non-severe COVID-19 patients was 58.28±101.8 and 94.69±114.22 respectively (SMD = 0.44; 95%CI: -0.78 to 1.66; p=0.48). SP-D levels also did not detect statistically significant differences in COVID-19 patients who survived and died in the hospital (27.18±16.4 vs. 29.12±14.14; SMD = 0.07; 95%CI: -0.28 to 0.42; p=0.70). Conclusions: Results of the current systematic review and meta-analysis indicated that SP-D may be a good marker for differentiating patients with COVID-19 from healthy patients, but it does not provide prognostic value among patients with COVID-19. Further studies are needed to confirm the results